Efficacy and safety of P2Y12 inhibitor monotherapy after complex PCI: a collaborative systematic review and meta-analysis. Issue 3 (23rd December 2022) - Nicolas, Johny; Dangas, George; Chiarito, Mauro; Pivato, Carlo A; Spirito, Alessandro; Cao, Davide; Giustino, Gennaro; Beerkens, Frans; Camaj, Anton; Vogel, Birgit; Sartori, Samantha; Yamamoto, Ko; et al.
Abstract: Aims: Complex percutaneous coronary intervention (C-PCI) is associated with an increased risk of ischaemic and bleeding complications. We aimed to assess the safety and efficacy of a 1–3-month dual antiplatelet therapy (DAPT) regimen followed by P2Y12 inhibitor monotherapy after C-PCI. Methods and results: We conducted a meta-analysis of randomized trials comparing a 1–3-month DAPT regimen followed by P2Y12 inhibitor monotherapy with standard (≥12 months) DAPT in patients undergoing C-PCI. C-PCI criteria and the co-primary bleeding and ischaemic outcomes were determined according to each trial. Secondary outcomes included major bleeding, all-cause death, myocardial infarction, and stent thrombosis. All outcomes were evaluated at 12 months after randomization. We used hazard ratios (HRs) and 95% confidence interval (CI) as a metric of choice for treatment effects with random-effects models. Among 8299 screened studies, five randomized trials fulfilled the eligibility criteria. In the pooled population of 34 615 patients, 8818 (25.5%) underwent C-PCI. As compared with standard DAPT, a 1–3-month DAPT regimen followed by P2Y12 inhibitor monotherapy reduced the bleeding risk in C-PCI (HR:0.66, 95% CI:0.44–0.98) and non-C-PCI (HR:0.60, 95% CI:0.45–0.79) patients ( P -interaction = 0.735). Furthermore, the risk for the primary ischaemic endpoint was similar in patients randomized to either arm, with significant effect modification by PCI complexity showing an enhanced benefit of 1–3-month DAPT in patients undergoing C-PCI (C-PCI, HR:0.69, 95% CI:0.48–1.00; non-C-PCI, HR:1.04, 95% CI:0.84–1.30; P -interaction = 0.028). Conclusion: As compared with a standard DAPT, a 1–3-month DAPT regimen followed by P2Y12 inhibitor monotherapy reduced bleeding complications after C-PCI without increasing the risk of ischaemic events. PROSPERO-registered (CRD42021259271) Graphical Abstract: